The Effect of Pollen Supplementation on the Recovery of Lactic Acid Levels and Heart Rate After 1 Hour of Submaximal Exercise - Wahyudi, Heri; Bawono, Mokhamad Nur; Pramono, Made; Sudijandoko, Andun; Dewi, Ratna Candra; Pudjijuniarto, Pudjijuniarto (Journal of Sport Science and Education, 2023)
This study aims to demonstrate that supplementation with pollen nutritional ingredients can enhance the rate of decrease in lactic acid levels and heart rate after 1 hour of submaximal exercise loading. The research methodology employed is experimental, utilizing a randomized one-group pre-test and post-test design. The sample consisted of 11 students from the Sports Science Study Program at Surabaya State University. Data analysis was conducted using the T-Test with a significance level of 0.05. The findings revealed a decrease in blood lactic acid levels and pulse rate after 1 hour of submaximal exercise. The percentage decrease in pulse rate was 91.541%, while the percentage decrease in blood lactic acid levels was 85.099%. However, it is important to note that comparing the percentage decrease in pulse rate to the percentage decrease in blood lactic acid levels may not be accurate due to the distinct nature of the two systems. Additionally, the supplement group demonstrated greater improvement compared to the control group, which did not receive supplements. Nonetheless, it should be acknowledged that both research variables had not fully returned to pre-exercise conditions.